1995
DOI: 10.1007/bf01245702
|View full text |Cite
|
Sign up to set email alerts
|

Influence of larvae and workers on egg production of queens of the pharaoh's ant,Monomorium pharaonis (L.)

Abstract: SummarySocial regulation of egg production and weight in queens was studied in relation to presence and absence of larvae and workers in the pharaoh's ant, Monomorium pharaonis (L.).Results were obtained by counting eggs and weighing queens under various conditions. The results confirm the existence of a positive feed-back loop between mated queens and their larvae as evident from a correlation (Y = 4.575 * X + 6.452) between the number of large worker larvae (X) and the egg yield (Y). This correlation seems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…The difference in number of oocytes within each group confirms a previously observed physiological effect of the large larvae by Børgesen and Jensen (1995) (Fig. 4).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The difference in number of oocytes within each group confirms a previously observed physiological effect of the large larvae by Børgesen and Jensen (1995) (Fig. 4).…”
Section: Discussionsupporting
confidence: 77%
“…Børgesen and Jensen (1995) found, however, that the effect of larvae on fecundity of queens is around 4.6 eggs per larva per day. When larvae were absent, the number of repletes helped the queen sustain egg laying but not as effectively as larvae.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other researchers have shown that only the number of late stage larvae is responsible for queen fertility in e.g. Monomorium pharaonis and Solenopsis invicta (Tschinkel, 1988;Børgesen & Jensen, 1995;Cassill & Vinson, 2007). This suggests that different mechanisms may operate in different ant species.…”
Section: Discussionmentioning
confidence: 76%
“…This suggests that the presence of later stage brood may stimulate queen fecundity. The presence of late stage larvae has been shown to trigger queen fecundity in S. invicta and Monomorium pharaonis (Tschinkel, 1988;Børgesen and Jensen, 1995;Cassill and Vinson, 2007), whereas the presence of cocoons was able to trigger fecundity in Camponotus spp. (Gibson and Scott, 1990).…”
Section: Discussionmentioning
confidence: 97%